Reinvestment, task complexity and decision making under pressure in basketball. (September 2015) - Kinrade, Noel P.; Jackson, Robin C.; Ashford, Kelly J.
Abstract: The aims of this study were to investigate choking susceptibility in a perceptual judgment task and to examine the predictive validity of the Decision Specific Reinvestment Scale (DSRS). A computer-based, choice response time basketball passing task was performed under low and high pressure conditions. Complexity was manipulated by depicting 3-on-3 and 5-on-5 scenarios. Repeated-measures ANOVAs revealed performance decrements under pressure with regard to response accuracy, moderated by task complexity, and a general speeding of performance over successive blocks. The DSRS was a significant predictor of poorer response accuracy under pressure in the high-complex task. Examination of the DSRS subscales revealed rumination as the only significant factor, predicting changes in response time and accuracy in the low- and high-complex versions of the task, respectively. Findings support the predictive validity of the DSRS, and highlight the importance of avoiding ruminative thoughts when making complex decisions under pressure. Highlights: Basketball players' decision-making accuracy deteriorated under pressure and was moderated by task complexity. The DSRS was a significant predictor of poorer response accuracy under pressure in the high-complex task. Rumination was the only significant factor, predicting changes in response time (low-complex) and accuracy (high-complex). Findings support the predictive validity of the DSRS. Underlines the importance of avoiding ruminative thoughts when making complex decisions under pressure.